KESESUAIAN LAHAN UNTUK PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) BERADSARKAN ANALISIS KEMIRINGAN LERENG DARI CITRA SATELIT RADAR DI KABUPATEN PANGKEP - Satriani, Yuni; Nurmiaty, Nurmiaty; Halid, Erna (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Sloped land or land slope is one of the limiting factors in the growth and production of corn, Characteristics of sloped land have limited ability to develop a type of crop, including corn plants in an agricultural area. The purpose of the study was to analyze the suitability of corn crop land based on slope slope for corn plant growth (Zea mays L.) on agricultural land in Pangkep district. The implementation of this research began in Desember2024, in Pangkep Regency. The technique used in this study uses Arc-GIS devices, contour digital data is cut with the administrative map of Pangkep Regency, so that contour digital data for the Pangkep Regency area is obtained. The conclusions that can be drawn from this study are, land suitability based on slope slope in Pangkajene Regency and the Islands, there are 43,768.86 ha of land that is very suitable (S1) for the development of corn crops, 5,178.06 ha of land that is quite suitable (S2), 12,341.37 ha of land that is marginally suitable (S3), and there are 18,564.52 ha of land that cannot be used at all (N) in the land of suitability for corn crops in Pangkep Regency. So that the total number of S1, S2, S3 and N is 80,032.82 h